More inequality, but less coverage: How and why TV news avoided ‘The Great Debate’ either side of the financial crisis 2008–14 - Richard Thomas (The Discursive Construction of Economic Inequality, 2020)
Despite inequality growing sharply, it has been largely ignored by broadcast media.